2022
DOI: 10.3389/fnagi.2022.966525
|View full text |Cite
|
Sign up to set email alerts
|

Exploring brain changes of impulse control disorders in Parkinson's disease: An ALE study

Abstract: BackgroundPrevious neuroimaging studies reported inconsistent results for comparison between Parkinson's disease (PD) with impulse control disorder (PD-ICD) and without ICD (PD-no ICD).MethodsA search was performed in databases (PubMed and Web of Science) to identify studies published before May 2022. An anatomic likelihood estimation (ALE) method study was made for neuroimaging studies in PD-ICD.ResultsThe study included 20 studies (including 341 PD-ICD and 437 PD-no ICD). PD-ICD patients showed significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Clinical observations suggest vulnerability to ICD differs across individuals. Vulnerability has been associated with structural and functional deficits in brain regions related to reward processing, such as the caudate nucleus (43). To explore whether differences in baseline disease severity predicted vulnerability to ICD in our mouse model, we correlated postmortem measures of dopaminergic cell body and axonal integrity with key quantitative measures ( K & A ) associated with the delay discounting curve (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical observations suggest vulnerability to ICD differs across individuals. Vulnerability has been associated with structural and functional deficits in brain regions related to reward processing, such as the caudate nucleus (43). To explore whether differences in baseline disease severity predicted vulnerability to ICD in our mouse model, we correlated postmortem measures of dopaminergic cell body and axonal integrity with key quantitative measures ( K & A ) associated with the delay discounting curve (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies tried to identify the risk factors for ICDs in PD and found a lot of potential contributors including demographic, disease-, treatment- and personality-related, addictive, cultural, psychiatric, and genetic factors among others 1 , 10 , 12 , 13 . However, at the same time, it is also acknowledged that ICDs are likely associated with specific structural and functional brain changes that may play a role in the diagnosis of ICDs in PD 15 . Based on our results, it appears that not only microscopic white matter changes, which require sophisticated methods for detection that are not usually part of clinical routine, but easy-to-assess macroscopic WMHs may also be associated with ICDs and might be an independent risk factor in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since the results are quite inconsistent across the studies, reviews and meta-analytic articles tried to integrate findings and recognize consistencies 14 17 . While a recent meta-analysis suggested significant cortical thinning in the right precentral, inferior- and middle frontal gyri, the left superior frontal and cingulate gyri of PD patients with ICD, this conclusion was based on only three studies 15 and other reviews revealed that morphometric findings are rather too inconsistent to reach any firm conclusion about the structural brain changes associated with ICD in PD 14 , 16 , 17 . A recent review of brain activity studies (including fMRI, PET and SPECT studies) suggested the involvement of ventral striatum, orbitofrontal cortex and anterior cingulate cortex (ACC), with the role of ventral striatum and ACC confirmed by activation likelihood estimation (ALE) meta-analysis as well 16 .…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, H. pylori eradication results in significant clinical improvement in the symptoms and better PD patient outcomes [ 66 , 67 , 68 ]. It is important to note that abnormal BCT may contribute to cognitive decline in patients with PD [ 69 , 70 ]. Furthermore, regarding glaucoma (defined as “ocular” AD), we reported a 2-year beneficial effect of H. pylori eradication on glaucoma progression, suggesting a possible causal link between this bacterium and glaucoma [ 45 , 71 ].…”
Section: Introductionmentioning
confidence: 99%